Ssams2, a Gene Encoding GATA Transcription Factor, Is Required for Appressoria Formation and Chromosome Segregation in Sclerotinia sclerotiorum - Liu, Ling; Wang, Qiaochu; Zhang, Xianghui; Liu, Jinliang; Zhang, Yanhua; Pan, Hongyu (Frontiers in Microbiology, 2018)
AMS2, amulticopy suppressor for the cpn1 (SpCENP-A) mutant, functions to specifically regulate histone genes transcription and chromosome segregation. As a cell-cycle-regulated GATA transcription factor in eukaryotic organisms, little research has been done on the role of AMS2 protein in pathogenic fungi. In Sclerotinia sclerotiorum, Ssams2 (SS1G_03252) encodes a protein which has been predicted to contain GATA-box domain. Here, Ssams2-silenced strains with significantly reduced Ssams2 gene expression levels exhibited defect in hyphal growth, hyphal branching patterns, compound appressoria differentiation and the oxalic acid production compared to the wild-type (WT) strain. By common bean leaves infection assays, we identified the role of Ssams2 in full virulence. Furthermore, the numbers of cell nucleus in the same length of mycelium in Ssams2-silenced transformants were significantly less than that in the WT strain. The expression levels of histone genes and cell cycle genes in transformants were down-regulated significantly in the RNAi strains. Taken together, our work suggests that the TF SsAMS2 is required for growth, appressoria formation, virulence, and chromosome segregation in S. sclerotiorum.